Less water renewal reduces effects on social aggression of the cichlid Pterophyllum scalare - Gauy, Ana Carolina dos Santos [UNESP]; Boscolo, Camila Nomura Pereira [UNESP]; Gonçalves-de-Freitas, Eliane [UNESP] (My University, 2018)
Changes in aquatic environments can affect fish behavior. Water renewal, for example, can dilute chemical signals, which are a social communication tool used by some fish species, and this dilution increases aggressive interactions in the group. Fierce and prolonged fights can affect fish welfare by increasing the probability of injuries, stress, and detrimental impacts on fish health. We tested whether the amount of water changed was associated with social aggression in the angelfish Pterophyllum scalare, a popular ornamental Amazonian cichlid. We designed an experiment with social groups (3 fish) that were assigned to one of three treatments (with 15 replicates of each treatment): 1) 50% water renewal; 2) 25% water renewal; or 3) 0% renewal (i.e., water removed and returned to the aquarium as a control). These treatments were referred to as T50%, T25%, and T0%, respectively. Fish behavior was video-recorded immediately before water renewal (baseline) and also 1 min, 1 h, 2 h, and 24 h after water renewal. The frequencies of attacks (overt fights) and displays (threats) were compared using the general linear model (GLM), with the treatment as the categorical factor, observation sessions as the repeated measures, and social rank as a continuous factor. Attacks increased after the water was changed, and they were higher in T50% than in T25% (P = 0.0001). In T25%, aggression returned to baseline levels after 1 h (P = 0.32), but remained increased after 24 h in T50% (P = 0.000001). Changing only a small volume of water at a time was therefore found to prevent exaggerated aggressive interactions among P. scalare specimens and to reduce the probability of injuries, stress, and detrimental impacts on fish welfare.
Keywords: Chemical communication; Ornamental fish; Social rank; Welfare